OBLIGATIONS DUE TO CAUSING HARM - Khakimova Rukhshona Burkhonovna (Bright Mind Publishing, 2025)
The article discusses the legal basis of obligations arising as a result of causing harm. The key principles of civil liability are analyzed, including the conditions for the occurrence of obligations, grounds for exemption from liability, and types of compensation for damage. Particular attention is paid to current trends in the regulation of tort obligations, including the impact of judicial practice.
Keywords: Obligations as a result of causing harm, tort liability, civil law, compensation for harm, causing harm, compensation for damage, judicial practice, legal regulation.